2010
DOI: 10.1073/pnas.0914638107
|View full text |Cite
|
Sign up to set email alerts
|

High-resolution human genome structure by single-molecule analysis

Abstract: Variation in genome structure is an important source of human genetic polymorphism: It affects a large proportion of the genome and has a variety of phenotypic consequences relevant to health and disease. In spite of this, human genome structure variation is incompletely characterized due to a lack of approaches for discovering a broad range of structural variants in a global, comprehensive fashion. We addressed this gap with Optical Mapping, a highthroughput, high-resolution single-molecule system for studyin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
209
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 169 publications
(211 citation statements)
references
References 43 publications
2
209
0
Order By: Relevance
“…For instance, the breakpoints of the inversions we mapped at Chr 16p12.3 showed >86% overlap with an inversion characterized in six independent studies using combinations of BAC clone sequencing, mate-pair sequencing, optical mapping, PCR, and FISH technologies (Supplemental Fig. S12; Tuzun et al 2005;Korbel et al 2007;Kidd et al 2008Kidd et al , 2010Pang et al 2010;Teague et al 2010). Of note, in some genomes from our population study, we observed multiple inversions with distinct genotypes at this locus (see Fig.…”
Section: Genome Research 1581mentioning
confidence: 96%
See 1 more Smart Citation
“…For instance, the breakpoints of the inversions we mapped at Chr 16p12.3 showed >86% overlap with an inversion characterized in six independent studies using combinations of BAC clone sequencing, mate-pair sequencing, optical mapping, PCR, and FISH technologies (Supplemental Fig. S12; Tuzun et al 2005;Korbel et al 2007;Kidd et al 2008Kidd et al , 2010Pang et al 2010;Teague et al 2010). Of note, in some genomes from our population study, we observed multiple inversions with distinct genotypes at this locus (see Fig.…”
Section: Genome Research 1581mentioning
confidence: 96%
“…Techniques such as karyotyping, fluorescence in situ hybridization (FISH), and optical mapping allow visualization and genotyping of inversions at the single-cell and single-chromosome level. However, the low resolution of these approaches limits their application to mapping large microscopic events that disrupt visible patterns (typically at the megabase-scale), and their low throughput limits the number of cells or individuals that can be studied at a time (Youings et al 2004;Zody et al 2008;Antonacci et al 2009;Feuk 2010;Teague et al 2010).…”
mentioning
confidence: 99%
“…In collaboration with various external groups, we identified and investigated reported path issues and associated assembly gaps using a combination of techniques, including optical maps (Teague et al 2010;Howe and Wood 2015), Strand-seq (Falconer et al 2012), admixture mapping (Genovese et al 2013a) and reevaluation of component sequences and overlaps (Mueller et al 2013). These analyses uncovered some substantial misassemblies in GRCh37 that spanned several megabases and many genes, including the regions at 1q21, 10q11, and a peri-centromeric inversion of Chromosome 9.…”
Section: Retilingmentioning
confidence: 99%
“…Important biomolecules, such as, chromosomal DNAs, or proteins whose functionalities are crucially dependent on the exact sequence of the nucleotides or amino acids usually exist in highly compact conformations. By straightening these molecules on a two dimensional sheet [2][3][4] or inside a nanochannel [5][6][7][8][9][10] it is possible to obtain the structural details of these molecules. It is believed that a complete characterization of the DNA sequence for each individual and a proper understanding the role of genetic variations will lead to personalized medicine for diseases, such as, cancer [11].…”
mentioning
confidence: 99%
“…Naturally quests for efficient but low cost techniques have attracted considerable attention. Along with optical maps [2,7], recently DNA melting characteristics inside a nanochannel have been studied showing further promises [9]. These recent experiments have generated renewed interests in theoretical and computational studies of confined polymers [13]- [24].…”
mentioning
confidence: 99%